Influence of the thickness of silicone registration material as a means for occlusal contact examination – an explorative study with different tooth clenching intensities. (29th July 2013) - Obara, R.; Komiyama, O.; Iida, T.; De Laat, A.; Kawara, M.
Summary: This study explored the influence of the thickness of silicone registration material on evaluation of the occlusal contact area and number of occlusal contact points, during increasing tooth clenching conditions in normal subjects. Twenty‐four subjects with no more than one missing tooth per quadrant participated. Surface electro‐myography was recorded from the masseter muscle. As a baseline measurement, intercuspal position was maintained with minimal force, and occlusal contact was recorded using blue silicone material. Occlusal contact was also recorded at 20% maximum voluntary contraction (MVC) and 40% MVC using visual feedback. The occlusal contact area and number of occlusal contact points were analysed using five levels of thickness of silicone registration material: Level 1 (0–149 μm); Level 2 (0–89 μm); Level 3 (0–49 μm); Level 4 (0–29 μm); and Level 5 (0–4 μm). The anterior part and the left and right posterior regions of the dental arch were analysed separately. At all detection levels, the occlusal contact area significantly increased from baseline to 20% MVC and to 40% MVC in the molar area ( P < 0·05). In the anterior part, the occlusal contact area significantly increased from baseline to 20% MVC and to 40% MVC only when using Level 5. The number of occlusal contact points significantly increased from baseline to 20% MVC and to 40% MVC only when using Level 5 in the molar area ( P < 0·05). It suggested that occlusal contacts may be different at low tooth clenching intensity with potential effects on the teeth or periodontal tissues.